2017
DOI: 10.1002/pon.4455
|View full text |Cite
|
Sign up to set email alerts
|

Clinician perspectives on symptom and quality of life experiences of patients during cancer therapies: Implications for eHealth

Abstract: Objective The purpose of this study was to explore clinician experiences with cancer symptom and quality of life (SQL) management from diagnosis throughout therapy in the ambulatory setting, plus identify preferences for a future SQL decision support system. Methods Eligible clinicians worked in ambulatory cancer care with responsibility for direct patient care. Focus groups were conducted to discuss symptom management throughout the treatment experience and features desired in a future decision support system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The nature and severity of symptoms experienced by patients was also not measured. The functionality to provide individually-tailored advice based on symptom severity has been identified as particularly important for the effectiveness of ePRO systems [46][47][48]. Similarly, the incorporation of clinician alerts to ePRO systems can increase clinician involvement in patient care and improve patient outcomes [25,29].…”
Section: Discussionmentioning
confidence: 99%
“…The nature and severity of symptoms experienced by patients was also not measured. The functionality to provide individually-tailored advice based on symptom severity has been identified as particularly important for the effectiveness of ePRO systems [46][47][48]. Similarly, the incorporation of clinician alerts to ePRO systems can increase clinician involvement in patient care and improve patient outcomes [25,29].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of this type of data synthesis mirrors work by Berry and colleagues, while investigating clinicians' perspectives of an e-health tool addressing symptoms and quality of life during cancer therapy. 65 The importance of interface functionality identified by the oncologists in this study, including ease of use and user-centered tailoring, is supported by the work of Puszkiewicz and colleagues 66 and Robertson and colleagues. 67 In both studies, researchers identified the importance of goals coming from a trusted source and the importance of data visualization.…”
Section: Discussionmentioning
confidence: 53%
“…The health professionals seem to wish for the development of an electronic monitoring in real time for symptom management. 60…”
Section: Discussionmentioning
confidence: 99%
“…The health professionals seem to wish for the development of an electronic monitoring in real time for symptom management. 60 However, it seems important to keep in mind that the implementation of such a tool should not be done to the detriment of the founding principles of palliative care. It is important to avoid the pitfalls of standardized care with the use of an app on the pretext of being more efficient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation